Regulatory T Cell Extracellular Vesicles Modify T-Effector Cell Cytokine Production and Protect Against Human Skin Allograft Damage - Tung, Sim Lai; Fanelli, Giorgia; Matthews, Robert Ian; Bazoer, Jordan; Letizia, Marilena; Vizcay-Barrena, Gema; Faruqu, Farid N.; Philippeos, Christina; Hannen, Rosalind; Al-Jamal, Khuloud T.; Lombardi, Giovanna; Smyth, Lesley Ann (Frontiers in Cell and Developmental Biology, 2020)
Regulatory T cells (Tregs) are a subpopulation of CD4+ T cells with a fundamental role in maintaining immune homeostasis and inhibiting unwanted immune responses using several different mechanisms. Recently, the intracellular transfer of molecules between Tregs and their target cells has been shown via trogocytosis and the release of small extracellular vesicles (EVs). In this study, CD4+CD25+CD127lo human Tregs were found to produce EVs capable of inhibiting the proliferation of effector T cells (Teffs) in a dose dependent manner. These vesicles also modified the cytokine profile of Teffs leading to an increase in the production of IL-4 and IL-10 whilst simultaneously decreasing the levels of IL-6, IL-2 and IFNγ. MicroRNAs found enriched in the Treg EVs were indirectly linked to the changes in the cytokine profile observed. In a humanised mouse skin transplant model, human Treg derived EVs inhibited alloimmune-mediated skin tissue damage by limiting immune cell infiltration. Taken together, Treg EVs may represent an exciting cell-free therapy to promote transplant survival.